(3GfXeI GdaG GdeMGSHjIs - (3JZQjO eajO cGed(B, (3HdjHdIs ((3YeGf(B:s (3OGQ GdMGeO(B,s, 2008)
-(3fXGe GdeMGSHI GdYGeI,fXGe eJGHYI GdYedGA,fXGe GdfbO hGdUfOhb,fXGe eJGHYI GdTjcGJ, fXGe GdGUhd GdKGHJI(B.s